Sekurytyzacja w sektorze publicznym - Hadro, Dominika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents the securitisation operation in public sector, which nowadays becomes more and more popular transaction in European countries. The analysis confirms that the proper conducted securitisation process by entities from public sector can have a fundamental influence on executing the resolves of Maastricht Treaty. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 151-157